Protein deficiency – a challenge to livestock productivity enhancement in Nepal - Singh, S. B. (Journal of Agriculture and Forestry University, 2020)
An assessment was made in 2019 to determine the crude protein (CP) supply situation for the livestock in Nepal. The land resources were assessed by utilizing the land use data generated by ICIMOD in 2010. The Land Resource Mapping Project (LRMP) (1986) remained the main source of data to estimate the CP supplies from these land resources (forests, shrub lands, grasslands, croplands, including weeds, and barren lands), plus kitchen wastes as animal feeds. Crop data of the Ministry of Agriculture and Livestock Development (MoALD) (2016/17) were utilized to estimate the CP supply from crop residues and milling by-products and the livestock data to estimate livestock feed requirements. The study findings revealed that there is critical shortage of CP in the livestock feeds across the eco-zones and across the provinces, with an overall deficit of 52.8%. The shortage reached about 60% in Province One and Three. The deficit in other provinces ranged from 37.6% to 52.6%. These deficits are mainly associated with the dependency of livestock production system on crop residues and low quality roughages. It is recommended that the future livestock development strategy focuses at encouraging farmers to replace the use of straws and stovers with improved forage or pasture and tree fodders. Likewise promotion of commercial silage production and development of productive partnerships with the feed millers for adequate production and supply of major imported poultry feed ingredients such as yellow maize and soybean are also important to consider.